USING CARTOONS AND ANIMATED FILMS IN TEACHING ENGLISH VOCABULARY AND GRAMMAR: AN IMRAD-BASED STUDY - Saidvaliyeva, Fotima (International Conference on Arts, Society & Humanities, 2026)
This study investigates how English vocabulary and grammar can be taught more successfully in EFL courses using cartoons and animated movies. This study investigates the effects of employing a few sequences from Ballerina (2016) as a teaching tool rather than solely depending on textbooks and rule-based explanations. Two groups of college students participated in a quasi-experimental design. According to the findings, students who engaged in film-based learning activities showed more motivation, improved comprehension of grammar in context, and enhanced vocabulary recall. According to the results, when accompanied by organized classroom activities, animated movies may turn language sessions into interesting and relevant learning experiences..